Divergent patterns of progression to AIDS after infection from the same source: human immunodeficiency virus type 1 evolution and antiviral responses. - Liu, S L (1997)
The rate of progression to AIDS in human immunodeficiency virus type 1 (HIV-1)-infected individuals is determined by a complex series of interactions between the host and virus. Here we evaluate virologic properties and host responses in two men near-simultaneously infected with HIV-1 from the same sexual partner--one individual progressed to AIDS in less than 2 years, and the other remains asymptomatic 3 years postinfection. Distinct neutralizing antibody and cellular immune responses were evident, with the slower progressor exhibiting generally stronger and broader responses, except for cytotoxic T-lymphocyte responses early in infection. Virtually identical, homogeneous virus populations were found in both patients in the first sample obtained; however, a second unrelated HIV-1 virus population was also found in the fast progressor. Whether the second population emanated from an additional source of infection or the two were transmitted from the original source could not be determined. The virus population in the slower progressor turned over and diversified rapidly, whereas both virus populations in the rapid progressor evolved at a much slower rate. In addition, the character of mutational changes underlying these diversities appeared to be distinct, with a bias for diversifying selection developing in the slower progressor and a reciprocal bias towards purifying selection maintained in both populations in the fast progressor. Thus, the rapid evolution that is a hallmark of HIV replication may be a reflection of strong host resistance against emerging virus variants and a longer period of asymptomatic infection. Furthermore, rapid progression was not linked to a collapse of any appreciable immune response following attainment of some threshold of antigenic diversity but rather to a failure to drive this diversification and a condition of relatively unimpeded expansion of variants with optimized replicative capacity within the host.